Atherogenic dyslipidemia in diabetic nephropathy: lipoprotein (a), lipid ratios and atherogenic index - MM, Suchitra; M, Sheshu Kumar; Bitla, Aparna R.; A, Madhusudhana Rao; S, Alok (International Journal of Research in Medical Sciences, 2017)
Background: Atherogenic lipid profile is reported to become pronounced with onset of nephropathy. Lipid ratios also indicate atherogenic dyslipidemia. Lipoprotein (a) [(Lp(a)] considered as an independent risk factor for cardiovascular diseases (CVD), may play an important role in development and progression of nephropathy in type 2 diabetes mellitus (T2DM). The present study aimed to assess atherogenic dyslipidemia in T2DM and diabetic nephropathy patients. Methods: Total cholesterol (TC), triglycerides(Tgl), high density lipoprotein (HDL), low density lipoprotein (LDL), very low density lipoprotein (VLDL), Lp(a), lipid ratios: TC/HDL, Tgl/HDL, LDL/HDL, non-HDL cholesterol and atherogenic index (AI) was assessed in T2DM (n=35), diabetic nephropathy (n=30) and healthy individuals (n=30). Means of biochemical parameters were compared by ANOVA (analysis of variance). Pearson correlation was performed to study the association between parameters. Receiver operating characteristics (ROC) curve analysis was done to assess the predictive ability of the variables. Results: Atherogenic dyslipidemia with elevated Lp(a), TC, Tgl, VLDL, LDL, non-HDL cholesterol, lipid ratios, AI and low HDL levels were observed in both T2DM patients with and without nephropathy when compared to controls. Significantly high Tgl/HDL, TC/HDL and AI were observed in diabetic nephropathy when compared to T2DM. Conclusion: T2DM and diabetic nephropathy are associated with dyslipidemia which was more pronounced in diabetic nephropathy. Elevated Lp(a) levels may be considered as an independent CVD risk marker in T2DM and diabetic nephropathy patients along with atherogenic lipid ratio indicators.